LEARN FROM PONDOK PESANTREN AS THE MEANS FOR BUILDING YOUNG MUSLIMS GENERATION’S IDENTITY - Aruni Chaerunisa; Firda Arifatu Rizkia; Nada Firdaus, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Education is the need of every human being. Education is useful for developing self-potential. One form of education in Indonesia is the education of Islamic boarding schools as known as Pondok pesantren. Pondok Pesantren do not only teach education at schools in general but also integrate the knowledge of Islam religion in the education system. Nowadays, the condition of young Muslims is very alarming due to the inability to face the flow of globalization and thus losing its Muslim identity. As the result, there is a moral decline that leads to deviant behavior, especially concerning Islamic values. To overcome this problem, Pondok Pesantren education can be a solution. In this study two samples of famous Pondok Pesantren in Indonesia were taken, namely Pondok Modern Darussalam Gontor and Pondok Pesantren Sidogiri. We use literature study methods from various journals that discuss the importance of Pondok Pesantren. As a step to deepen the material, an interview was held with an Ustadz (Islamic religious teacher) who had conducted research at various Pondok pesantren in Indonesia. The results of this study, obtained 3 values and teaching lifestyles that can be applied from Pondok Pesantren, namely the formation of identity, sensitivity to society, and efforts to make changes in society without losing identity. The two Pondok Pesantren teach the formation of a good identity to their santri (students of pesantren) so that they are not easily carried away by the negative effects of globalization. In addition, it also teaches how to behave socially in the community so that they can apply the knowledge gained in Pondok Pesantren and become agents of change in people's lives. Thus, the education system of Pondok Pesantren can be used as a means of forming the identity of young Muslims as a provision to face the current of globalization.